(untitled) (Bangladesh Journal of Agricultural Research, 2017)
Hayman’s component analysis was employed to estimate genetic components of variation for yield and yield related traits in boro rice. Nine diverse lines of boro rice were crossed in diallel mating design excluding reciprocals and all the parental lines along with their 36 crosses were evaluated in randomized block design over 3 seasons in 3 replication. Significant differences among genotypes were observed for all the traits over seasons. Component analysis indicated importance of both additive and dominance components. However, greater magnitude of dominance component than its corresponding additive component of variance exhibited greater role of dominance in the inheritance of these traits. The average degree of dominance was more than unity indicating overdominance for all the traits. Most of the traits exhibited low to moderate narrow sense heritability. Bangladesh J. Agril. Res. 42(3): 457-466, September 2017